Strategi Pemasaran UMKM di Desa Sumber Rahayu Kecamatan Rambang Kabupaten Muara Enim - Puspa Utami; Rian Febriansyah (Program Studi Perbankan Syariah, 2024)
This research is motivated by the intense competition between Micro, Small and Medium Enterprises (MSMEs) in attracting consumer interest in products so that they can increase their business competitiveness. One way that can be done is to implement a marketing strategy. The research approach used is qualitative research which uses descriptive research. The method used in collecting data is observation, in-depth interviews and documentation. The research results show that first, the marketing strategy used by MSME grocery stores in Sumber Rahayu Village is market segmentation, market target, market position, and marketing mix. Second, there are opportunity and threat factors that influence the marketing strategy of MSME grocery stores in Sumber Rahayu Village. Third, the number of production and number of sales of MSME products in grocery stores in Sumber Rahayu Village has increased from year to year.